China's Impacton World Commodity Markets - Roache, Shaun (IMF Working Papers; Working Paper, 2012)
Shocks to aggregate activity in China have a significant and persistent short-run impact on the price of oil and some base metals. In contrast, shocks to apparent commodity-specific consumption (in part reflecting inventory demand) have no effect on commodity prices. China's impact on world commodity markets is rising but, perhaps surprisingly, remains smaller than that of the United States. This is mainly due to the dynamics of real activity growth shocks in the U.S, which tend to be more persistent and have larger effects on the rest of the world.